IgM Deficiency in Autoimmune Blistering Mucocutaneous Diseases Following Various Treatments: Long Term Follow-Up and Relevant Observations - Ahmed, A. Razzaque; Aksoy, Merve (Frontiers in Immunology, 2021)
IgM deficiency has been reported in patients with many autoimmune diseases treated with Rituximab (RTX). It has not been studied, in detail, in autoimmune mucocutaneous blistering diseases (AIMBD). Our objectives were: (i) Examine the dynamics of IgM levels in patients with and without RTX. (ii) Influence of reduced serum IgM levels on clinical and laboratory parameters. (iii) Explore the possible molecular and cellular basis for reduced serum IgM levels. This retrospective study that was conducted in a single-center from 2000 to 2020. Serial IgM levels in patients with five AIMBD (Pemphigus Vulgaris, Pemphigus Foliaceus, Bullous Pemphigoid, Mucous Membrane Pemphigoid, and Ocular Cicatricial Pemphigoid) were examined in 55 patients treated with RTX, IVIG, and conventional immunosuppressive therapy (CIST). The incidence of decreased IgM in patients treated with RTX was 19.6%. In patients treated with IVIG and CIST, it was 52.8% in 55 patients. IgM levels in the post-RTX group were statistically significantly different from the IVIG group (p<0.018) and CIST group (p<0.001). There were no statistically significant differences between the groups in other clinical and laboratory measures. Decreased serum IgM did not affect depletion or repopulation of CD19+ B cells. Patients in the three groups achieved clinical and serological remission, in spite of decreased IgM levels. Decrease in IgM was isolated, since IgG and IgA were normal throughout the study period. Decreased IgM persisted at the same level, while the patients were in clinical remission, for several years. In spite of persistent decreased IgM levels, the patients did not develop infections, tumors, other autoimmune diseases, or warrant hospitalization. Studies on IgM deficiency in knockout mice provided valuable insights. It is clear that milieu, physical location, and possibly microenvironment influence the functions of peritoneal B cells in IgM production and regulation. There is no universally accepted mechanism that defines decreased IgM levels in AIMBD. The data is complex, multifactorial, sometimes contradictory, and not well understood. Nonetheless, data in this study provides novel information that enhances our understanding of the biology of IgM in health and disease.